HERITAGE MANAGEMENT: THE CASE OF TWO BAROQUE CHURCHES IN ILOCOS REGION, PHILIPPINES - Ferdinand Jermice Lamarca (SAMPURASUN, 2017)
Four Baroque Roman Catholic churches constructed between the 16th and the 18th centuries during the Spanish period of the Philippines are inscribed in the UNESCO World Heritage List. Two of them are assessed in this study. Generally, the paper aimed to assess the management of the two baroque churches in Region I, Philippines, to wit: the Paoay Church and and Sta. Maria Church. Specifically, it sought to 1) identify the reason for their inscription; 2) discuss the laws and ordinances that provide for the protection and conservation of these sites; 3) discuss how the protection and conservation of these sites are administered; and 4) and determine the extent of the compliance by these sites of the requirements of protection and conservation. There are laws, international and national as well as ordinances passed at the local levels to provide protection and preservation of the heritage sites. The Paoay Church is managed by the following groups, to wit: 1) Paoay Church Restoration Task Force; 2) Municipal Government; 3) Homeowners Association within the Heritage District; and 4) Other NGOs. The Sta. Maria Church, on the other hand, is managed by the different groups that comprise the Sta. Maria Heritage District Council. As conclusions, there are adequate laws to protect the heritage sites. But some provisions are not strictly enforced. The LGUs are very supportive. However, their participation, particularly in Sta. Maria is constrained by lack of funds. Parish priests play a very significant role in the preservation of these churches. Their competence or enlightenment on conservation efforts would spell their success or failure.